1979
DOI: 10.1080/15298667991429813
|View full text |Cite
|
Sign up to set email alerts
|

The clearance of cadmium aerosols after I inhalation exposure

Abstract: CdO and CdCl2 aerosols were inhaled by two groups of rats and their subsequent clearance behaviour was studied. The half-life of the long term lung clearance rates was identical for both compounds, namely 67 days. For CdO, an initial faster clearance was observed, whereas the initial clearance of CdCl2 did not differ from its long term clearance rate, resulting in a relatively higher Cd burden of the lung in the CdCl2 study. Cd liver and kidney concentrations were also higher in the CdCl2 study, originating fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The induction of metallothionein synthesis by cadmium in liver and kidneys might be responsible for the retention of cadmium in these organs. A similar pulmonary clearance and extrapulmonary tissue distribution of inhaled cadmium aerosol and of intratracheally instilled cadmium oxide have been observed earlier (Boisset et al 1978;Henderson et al 1979;Oberdoerster 1979;Hadley et al 1980 appears to be due to haemorrhage and inflammatory oedema followed by reparative proliferative processes in lungs (Cross e t a / . 1979).…”
Section: Discussionsupporting
confidence: 74%
“…The induction of metallothionein synthesis by cadmium in liver and kidneys might be responsible for the retention of cadmium in these organs. A similar pulmonary clearance and extrapulmonary tissue distribution of inhaled cadmium aerosol and of intratracheally instilled cadmium oxide have been observed earlier (Boisset et al 1978;Henderson et al 1979;Oberdoerster 1979;Hadley et al 1980 appears to be due to haemorrhage and inflammatory oedema followed by reparative proliferative processes in lungs (Cross e t a / . 1979).…”
Section: Discussionsupporting
confidence: 74%
“…However, the same study reported significantly reduced liver-to-body weight ratios in the food-restricted animals, while the heart-, spleen-, and kidney-to-body weight ratios were unchanged from control values, indicating the changes observed after Cd exposure may be treatmentrelated. Although effects of Cd on the spleen have not been reported, Cd accumulation in the liver, kidneys, and heart has been documented (Fischer and Thind, 1971;Amacher and Ewing, 1975;Boisset et al, 1978;Ohanian et al, 1978;Prigge, 1978;Oberdoerster et al, 1979). In one of these studies (Boisset et al, 1978) Cd accumulation in the liver and kidney was accompanied by increased organ-to-body weight ratios, while in another (Ohanian et al, 1978) this did not appear to be the case.…”
Section: Discussionmentioning
confidence: 88%
“…Toxicity is affected not only by Cd concentration but also by the form, this is probably related to solubility. The bioavailability of Cd is dependent on the solubility 11) . On acute exposure, the bioavailabilities and the toxicity of more soluble Cd compounds are higher than those of less soluble Cd compounds after rapid absorption in blood by inhalation exposure 12) .…”
Section: Discussionmentioning
confidence: 99%